Multisource inverse‐geometry CT. Part II. X‐ray source design and prototype. Issue 8 (18th July 2016) - Neculaes, V. Bogdan; Caiafa, Antonio; Cao, Yang; De Man, Bruno; Edic, Peter M.; Frutschy, Kristopher; Gunturi, Satish; Inzinna, Lou; Reynolds, Joseph; Vermilyea, Mark; Wagner, David; Zhang, Xi; et al.
Abstract : Purpose: This paper summarizes the development of a high‐power distributed x‐ray source, or "multisource, " designed for inverse‐geometry computed tomography (CT) applications [see B. De Man et al., "Multisource inverse‐geometry CT. Part I. System concept and development, " Med. Phys.43, 4607–4616 (2016)]. The paper presents the evolution of the source architecture, component design (anode, emitter, beam optics, control electronics, high voltage insulator), and experimental validation. Methods: Dispenser cathode emitters were chosen as electron sources. A modular design was adopted, with eight electron emitters (two rows of four emitters) per module, wherein tungsten targets were brazed onto copper anode blocks—one anode block per module. A specialized ceramic connector provided high voltage standoff capability and cooling oil flow to the anode. A matrix topology and low‐noise electronic controls provided switching of the emitters. Results: Four modules (32 x‐ray sources in two rows of 16) have been successfully integrated into a single vacuum vessel and operated on an inverse‐geometry computed tomography system. Dispenser cathodes provided high beam current (>1000 mA) in pulse mode, and the electrostatic lenses focused the current beam to a small optical focal spot size (0.5 × 1.4 mm). Controlled emitter grid voltage allowed the beam current to be varied for each source, providing the ability to modulate beam current across the fan of the x‐ray beam, denoted as a virtual bowtie filter. The custom designed controls achieved x‐ray source switching in <1 μ s. The cathode‐grounded source was operated successfully up to 120 kV. Conclusions: A high‐power, distributed x‐ray source for inverse‐geometry CT applications was successfully designed, fabricated, and operated. Future embodiments may increase the number of spots and utilize fast read out detectors to increase the x‐ray flux magnitude further, while still staying within the stationary target inherent thermal limitations.